Tennessee Fish Fry - Arthur Schwartz::::::::: (Chappell & Co. Inc.)
Piano score, 5 p. On cover: New York Worlds Fair of 1940 presents Albert Johnsons production of American Jubilee. Lyrics and music by Oscar Hammerstein IInd and Arthur Schwartz. Staged by Leon Leonidoff dances by Catherine Littlefield costumes by Lucinda Ballard musical director Don Voorhees, with Lucy Monroe and a cast of 350. Publishers advertisement on verso of last leaf.